Exploring non-education faculty’s lived teaching experiences in a Philippine higher education institution - Limen, Julanie M.; Arante, Ramil B. (International Journal of Evaluation and Research in Education (IJERE), 2025)
This qualitative, phenomenological study investigates the impact of lacking formal pedagogical training on non-education faculty in the context of Caraga State University Cabadbaran Campus (CSUCC). The research explores their lived experiences to understand the specific challenges and coping mechanisms they employ in their teaching roles. Data was collected through in-depth interviews and focus group discussions with a purposive sample of ten non-education faculty members representing various disciplines at CSUCC. The sample size of 10 participants was determined by the principle of data saturation, ensuring the collection of rich and recurring data to identify significant themes. Several key themes emerged through thematic analysis of the transcribed interviews and focus group discussions. These included self-perceived teaching efficacy, difficulties encountered in test construction and syllabus design, challenges related to student engagement, and the utilization of available resources and support systems. The findings of this study provide valuable practical implications for higher education institutions (HEIs). They suggest the necessity of implementing targeted training programs, offering relevant professional development opportunities, and establishing dedicated resources to support non-education faculty better. Ultimately, these interventions aim to enhance teaching quality, improve faculty satisfaction, and foster a more supportive teaching and learning environment.